CAPABILITY TO MANAGE FINANCIAL REPORTS FOR MSMES UTILIZING ACCOUNTING INFORMATION SYSTEMS - Agry Alfiah; Asri Ady Bakri; Fatimah Fatimah; Rinto Syahdan; Hedar Rusman (SEAN Institute, 2023)
Accounting Information Systems (AIS) are gaining importance in the management of financial reports for micro, small, and medium-sized enterprises (MSMEs) in the current digital era. The ability to effectively utilize AIS can help SMBs manage their finances more efficiently and precisely, thereby enhancing their performance and long-term success. By utilizing the appropriate AIS, MSMEs can obtain advantages such as more efficient and accurate transaction recording, improved financial analysis, and the ability to generate comprehensive and simple-to-understand financial reports. Utilizing accounting information systems, this study seeks to facilitate the management of financial reports from micro, small, and medium-sized enterprises. AIS is a system used to manage financial data and provide business proprietors with accurate and up-to-date financial information. By utilizing AIS, MSMEs can save time and energy when managing financial reports and making structured business decisions regarding data input and processing, particularly financial reports. The research yields an accounting information system with system features suitable for assisting and supporting MSMEs in managing financial management, such as managing customer data, sales data, purchase data, account data, general journal data, user data, sales reports, purchase reports, general journal reports, balance sheet reports, income statements, and capital change reports.